ANALISIS PEMBUATAN KONTRAK JUAL BELI ONLINE DALAM TRANSAKSI E-COMMERCE DITINJAU DARI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Muhammad Rafi Ismail; Agri Chairunisa Isradjuningtias (The Juris, 2022)
The rise of Internet and social media users in Indonesia has made e-commerce (online) business transactions grow. The increasing number of buying and selling online indirectly also has an impact on the development of the rule of law. In running an online business or conducting online transactions, there are several legal aspects of e-commerce and buying and selling online or electronically that must be known. Online transactions are usually interpreted as electronic contracts, namely legal ties or relationships that are carried out electronically which combine networks of computer-based information systems with systems. Online buying and selling was born because of a buying and selling contract that occurs electronically between the seller and the buyer. However, until now the rules of electronic buying and selling are still not clearly written in the law that applies in the territory of Indonesia. This is because the legal terms of electronic agreements have not been specifically regulated. In principle, the rules are contained in the Civil Code, which is a reference in making contracts for online buying and selling transactions. As long as this contract is made in compliance with the 4 legal terms of the agreement referred to in the Civil Code, the online transaction contract can be considered valid and binding on sellers and buyers.